Mary Parker Follett's Footprints in the Management Principles of Today and the Future - Nurcan Akbaş; Bahar Taner (Istanbul Management Journal)
Mary Parker Follett’s management philosophy and principles at the beginning of the 20th century exhibit the characteristic of management models of the past, present and future, and they appear to be linked to current theories of management. The aim of this research is to define the connection between Mary Parker Follett's management philosophy and past, present and expected future management approaches and to make a contribution to the science of management in this sense. For this purpose, this study seeks to investigate the relationship between, and similarities of, Follett’s management principles of those of matriarchal societies as the first social structures inancient times. The study also seeks to evaluate the basic concepts of management theories which have emerged since the industrial revolution. A narrative approach was applied in this study. The research findings indicate that Mary Parker Follett's management philosophy serves as a link between the management practices of the past, present and future and presents solutions to today's organizational, industrial, societal and international management problems. Through adopting Follett's management philosophy, humanity might be able to open the doors to a world with more freedom, peace, justice, equality and sharing. This in turn might give way to more happiness, more peacefulness, and high value of creativity in society.